Comprehensive health assessment of retired martial arts athletes: bone density, dietary intake, physical activity, and wellbeing - Alshaer, Tasneem; Battikhi, Nihad; Amawi, Adam Tawfiq; Trabelsi, Khalid; Jahrami, Haitham; Bouedo, Philippe; Ghazzawi, Hadeel Ali (Frontiers in Aging, 2025)
Regular physical activity offers benefits like enhanced bone density, which often persists post-retirement. However, retirement can lead to weight gain and changes in quality of life due to reduced physical activity. Therefore, this study investigates the long-term effects of elite athletic experience by comparing retired Jordanian male elite athletes (ages 40–50) with non-athletes of the same age. The differences were explored in weight changes, bone density, quality of life, happiness, stress, insomnia, physical activity, and dietary intake to understand how martial arts impact these health dimensions.MethodsA descriptive case-control study was conducted among 30 retired male elite athletes and 20 age-matched non-athletes. Bone density and body composition were measured using dual-energy X-ray absorptiometry (DEXA) scans. Additional assessments included anthropometric measurements, a 3-day dietary recall, physical activity (International Physical Activity Questionnaire), quality of life (WHOQOL), happiness (Subjective Happiness Scale), stress (Perceived Stress Scale), and insomnia (Insomnia Severity Index).ResultsRetired athletes showed significantly higher Z-scores for the left femur (neck and total) and the AP spine, with p-values <0.05. Among non-athletes, 65% had normal bone density with a Z-score ≥ −1.9 and a T-score > −1.1, 20% had abnormal bone density with a Z-score < −1.9, and 15% had osteopenia with a T-score between −1.1 and −2.4. In contrast, 100% of retired athletes had normal bone density with a Z-score ≥ −1.9 and a T-score > −1.1. Retired athletes exhibited greater weight changes than non-athletes, with a p-value <0.05; the average weight gain among retired athletes was 18.548 kg, and the mean weight gain among non-athletes was 4.3 kg. There were statistically significant mean differences in perceived stress levels between retired athletes and non-athletes with a p-value <0.05. In contrast, there were no statistically significant mean differences between the groups in quality of life, subjective happiness, and the Insomnia Severity Index.ConclusionThe study reveals that retired elite athletes maintain better bone density but face greater weight gain and stress than their non-athlete counterparts. Both groups enjoy a high quality of life and low levels of insomnia. These findings underscore the importance of continued physical activity for health and suggest that both retired athletes and non-athletes should adopt a balanced lifestyle to manage weight and stress effectively.